Spreading Influence Through Weak Ties: Cosponsorship, Legislative Networks, and Bill Success in Fragmented Congresses. Issue 2 (30th October 2018) - Skigin, Natán
Abstract : Literature on legislative success tends to focus on independent variables of which lawmakers have scarce control. This article analyzes instead how legislators' strategies affect their success in Congress. I posit that while weak ties between congresspeople are the most useful in increasing success in the chamber of origin under majoritarian settings, they do not raise the likelihood of bill approval in the second chamber or in plurality‐led legislatures. Building on a data set that contains all bills proposed to the Argentine Congress between 1983 and 2007, results support these context‐dependence hypotheses. I then use data from the Uruguayan Congress (1995–2010) to explore how the argument plays out in a Latin American legislature with weaker gatekeeping rules (i.e., an "open sky" legislature). Findings help gain insight into the strategies used in environments different from that of the widely studied U.S. Congress.